Adressatenspezifische Gestaltung von Fachvorlesungen im Lehramt: eine Fallstudie als Anstoß für vertiefte Reflexionen (mathematica didactica, 2021)
At the University of Vienna the subject matter education of teacher trainees has been completely separated from that of professional students of mathematics, beginning with the academic year 2014/15. This special feature allows for an additional freedom in designing subject matter courses in the teacher’s curriculum. The present project works out criteria that mathematics lecturers name as im-portant for their planning of the respective courses.